PENTINGNYA ILMU HUKUM DALAM KEHIDUPAN BERMASYARAKAT DI INDONESIA - Winanda, I Kadek Tampan Nova; Si Ngurah Ardhya; Kusuma, Putu Riski Ananda (Jurnal Ilmu Hukum Sui Generis, 2025)
The state of Indonesia is a state of law, which means that Indonesia establishes the law as the basis of power in the state and the legal administrator of its power is also exercised in the rule of law. Law is a law that regulates the way in which state or government instruments carry out their duties and obligations properly, so that their application can be accepted by the community. In this case the law is very important for the whole community, because the law makes the country better and more prosperous. Law is used as a regulator, servant, and protector of society. Therefore, the law is expected to be a forum for justice for all Indonesian people.